Development of a chicken-derived antivenom against the taipan snake (Oxyuranus scutellatus) venom and comparison with an equine antivenom. (15th September 2016) - Navarro, Diego; Vargas, Mariángela; Herrera, María; Segura, Álvaro; Gómez, Aarón; Villalta, Mauren; Ramírez, Nils; Williams, David; Gutiérrez, José María; León, Guillermo
Abstract: A chicken-derived antivenom (ChDAv) towards taipan snake ( Oxyuranus scutellatus ) venom was produced by purifying anti-taipan IgY from egg yolks of hens immunized with taipan venom. The productivity, antivenomic profile, neutralization ability, pharmacokinetic properties and immunogenicity of the ChDAv were compared with those of an antivenom produced in horses (EDAv). We found that 382 eggs are required to produce the mass of anti-taipan antibodies contained in one liter of equine hyperimmune plasma, and that 63 chickens would be needed to generate the amount of anti-taipan antibodies annually produced by one horse. It was estimated that, in Costa Rica, the production of anti-taipan antibodies could be 40% cheaper if chickens were used as immunoglobulin source, instead of horses. During antivenomic assessment, ChDAv showed lower ability to immunocapture the α subunit of taipoxin, the most important neurotoxin in the venom. ChDAv showed a lower ability to neutralize the coagulant and lethal activities of taipan venom. ChDAv was more immunogenic in rabbits than EDAv, probably due to the fact that chickens are phylogenetically more distant to rabbits than horses. This finding may explain why clearance from rabbit bloodstream was faster for chicken-IgY than for equine-IgG in a pharmacokinetic study. In conclusion, the production of anti-taipan antivenom was less effective when chicken egg yolks were used as source of immunoglobulins instead of horses. Highlights: Chicken (ChDav) and equine (EDaV) antitaipan antivenoms were compared. ChDAv has lower ability to immunocapture and neutralize the taipan venom. ChDAv was more immunogenic in rabbits than EDAv. ChDav was cleared faster than EDAv in a rabbit pharmacokinetic model. ChDAv is less effective than EDav.